America's great road trips and scenic drives [videorecording (DVD)] - Thomas, Peter, 1924-2016; Fox, Steve, 1948-; Wessel, Stanley (Reader's digest classic collection., 2009)
Driving tour of the United States, from Old Faithful's eruptions to New England's fall foliage. Cruise the Eastern Seaboard's scenic routes, discover America's heartland, see the American West, the picturesque countrysides and back roads.